Comparative analysis of antibiotic exposure association with clinical outcomes of chemotherapy versus immunotherapy across three tumour types. Issue 5 (7th September 2020) - Kulkarni, Amit A; Ebadi, Maryam; Zhang, Shijia; Meybodi, Mohamad A; Ali, Alaa M; DeFor, Todd; Shanley, Ryan; Weisdorf, Daniel; Ryan, Charles; Vasu, Sumithira; Rashidi, Armin; Patel, Manish Ramesh
Abstract : Background: In solid tumours, antibiotic use during immune checkpoint inhibitor (ICI) treatment is associated with shorter survival. Following allogeneic haematopoietic cell transplantation (allo-HCT), antibiotic-induced gut microbiome alterations are associated with risk of relapse and mortality. These findings suggest that the gut microbiota can modulate antitumour immune response across tumour types, though it is not clear if the impact on outcomes is specific to immune therapy. An important limitation of previous studies is that the analysis combined all antibiotic exposures irrespective of the antibiotic spectrum of activity. Whether antibiotic exposure during induction chemotherapy in acute myeloid leukaemia (AML) affects risk of relapse is also unknown. Patients and methods: We performed a single-centred retrospective analysis of antibiotic exposures in metastatic/advanced non-small cell lung cancer (NSCLC) and renal cell cancer (RCC) receiving ICI and newly diagnosed AML patients receiving induction chemotherapy achieving a complete remission 1. Antibiotic use within 4 weeks before and 6 weeks after the ICI initiation were included. In AML patients, antibiotic exposures between days 1 and 28 of induction were collected. Antibiotics were a priori stratified based on spectrum of activity. Primary outcomes of interest were progression-free survival (PFS), overall survival (OS) in NSCLC and RCC and relapse-free survival (RFS) in AML. Results: 140 patients with NSCLC, 55 with RCC and 143 with AML were included. In multivariable analysis, PFS and OS were shorter in NSCLC patients who received broad-spectrum anti-anaerobes (PFS, HR=3.2, 95% CI 1.6 to 6.2, p<0.01; OS, HR=1.7, 95% CI 0.8 to 3.6, p=0.19) or 'other' antibiotics (vancomycin-predominant) (PFS, HR=2.4, 95% CI 1.3 to 4.6, p<0.01; OS, HR=2.4, 95% CI 1.2 to 4.7, p=0.01). In RCC, patients who received penicillins/penicillin-class/early-generation cephalosporins had shorter PFS (HR=3.6, 95% CI 1.7 to 7.6, p<0.01) but similar OS (p=0.37). In the AML cohort, none of the exposures were associated with RFS. Conclusion: In contrast to AML, antibiotic exposures in solid tumours affected clinical outcomes. The presence of an allogeneic effect (allo-HCT) or an augmented immune system (checkpoint blockade) may be necessary for microbiota mediation of relapse risk.